PSYCHOCHEMICAL CHARACTERISTICS OF SNACK BAR MADE FROM MANGROVE FRUIT API-API FLOUR (Avicennia marina) - Zenadine, Muhammad Fairuz; Sulistiyati, Titik Dwi; Hardoko, Hardoko; Puspitasari, Yunita Eka (Jurnal Perikanan Unram, 2024)
Consuming snack bar with high sugar content and low fiber cause degenerative disease. Mangrove fruit api-api Avicennia marina is consumed as traditional food by mangrove society regarding to bioactive compounds of its. Therefore, snack bar is added mangrove fruit flour api-api (Avicennia marina) to increase the nutrition and to produce functional food. The purpose of this study was to characterize physochemical of snack bar formulated with mangrove fruit flour api-api (Avicennia marina). This study was conducted into two steps such as determination the proportion dry material and wet material, formulation snack bars added mangrove fruit flour api-api (Avicennia marina). The proportion of dry and wet material were 55:45 and 65:35. The best proportion of treatment was 55:45. The concentration mangrove fruit flour api-api (Avicennia marina) was 0%, 5%, 10% and 15%. Additional mangrove fruit flour api-api (Avicennia marina) 5% was significantly different in snack bar formulation with physichocemical characteristic such as texture 191.34; lightness 45.066; redness 9.27; dan yellowness 43.99; carbohydrate content 54,052. Proximate analysis was moisture 24,05%, ash content 1.50%, protein content 9.37%, lipid content 9.05%, and carbohydrate content 54,20%. Organoleptic analysis was colour 3.564, aroma 3.564, flavor 3.592, and texture 3.456.